2014
DOI: 10.4236/ojcm.2014.42011
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Fracture Toughness Evaluation of Poly(L-lactide acid)/Natural Fiber Composite by Using Double Shear Test Method

Abstract: In this work, interfacial fracture toughness between treated fiber and matrix was investigated by using double shear test method. Susrface treatment on the oil palm empty fruit bunch (OPEFB) fibers was performed to improve the interfacial bosnding properties of natural fiber reinforced Poly(L-lactide acid) composites. Three fibers model composite and four fibers model composite were prepared for the double shear test. The interfacial fracture toughness of both model composites is dependent on matrix length. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…The greater the length of the matrix, the higher the interfacial fracture toughness becomes. This finding is similar to the results reported by Chin Von Sia [42]. The highest G i value obtained for the untreated fiber was only 27.4 J/m 2 , which was much smaller than the 1 h, 2 h, 4 h, and 8 h alkali-treated Typha spp.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The greater the length of the matrix, the higher the interfacial fracture toughness becomes. This finding is similar to the results reported by Chin Von Sia [42]. The highest G i value obtained for the untreated fiber was only 27.4 J/m 2 , which was much smaller than the 1 h, 2 h, 4 h, and 8 h alkali-treated Typha spp.…”
Section: Resultssupporting
confidence: 90%
“…The strain energy of the model composite specimen can be calculated by adapting the mathematical model used by Sia et al [42], as follow:U=Ui +Uii+Uiii…”
Section: Methodsmentioning
confidence: 99%
“…Test results showed that composite filaments have better mechanical properties than PLA samples [ 100 ]. Sia et al (2014) investigated the toughness of the mode II interfacial fracture of a PLA matrix composite and oil palm empty fruit bunch (OPEFB) fibers, following a surface treatment with a NaOH solution, to improve the bonding interface of the composite [ 108 ].…”
Section: Materials For Fff Technologymentioning
confidence: 99%